Pengaruh Kompensasi dan Motivasi Terhadap Kinerja Karyawan Gen Z di Kudus - Muhammad Wahyu Riyadi; Muhammad Danial Firdaus Musyafak; Shofi Nadhif; Muhammad Qoes Atieq (J-MSDM (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2025)
This study aims to examine the influence of compensation and motivation on the performance of Generation Z (Gen Z) employees in Kudus Regency. Gen Z is known for its unique characteristics in the workplace, including high expectations for fair compensation and a strong need for motivation and recognition. This research employed a quantitative approach using a survey method, with questionnaires distributed to 81 respondents who are permanent Gen Z employees in various companies in Kudus. The data were analyzed using multiple linear regression analysis. The results indicate that both compensation and motivation have a positive and significant partial effect on employee performance. The significance value for compensation is 0.000 and for motivation is 0.010 (both < 0.05), suggesting that each variable individually influences performance. However, the simultaneous test (F-test) shows that the two variables do not significantly affect performance when considered together (Sig. = 0.102 > 0.05). The coefficient of determination (R²) value is 0.612, indicating that 61.2% of the variance in employee performance can be explained by compensation and motivation. This study contributes to the development of human resource management strategies that are more adaptive to the characteristics of Gen Z. The findings are expected to serve as a reference for companies in designing compensation and motivation systems that align with the expectations of the younger workforce to improve overall performance.